THE VES-CPP AND VES METHODS APPLICATION FOR THE ESTIMATION OF FILTRATION PROPERTIES OF CARBONATE ROCKS OF THE UPPER CRETACEOUS AND KARST DETERMINATION (ON THE EXAMPLE OF THE SITE “RAFALOVSKA”) - VYZHVA, S.; NURMUKHAMEDOV, V.; KACHAN, I.; REVA, M.; RASOVSKYI, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
By results of parametrical vertical electric sounding provided by the phase method of caused polarization (VES-CPP) are revealed dependences of polarization carbonate rocks top chalk from their filtration properties and lithological structure. Complex using of specific resistance and polarization allows predicting confidently the places of possible karst-buildings which result from inflows and migration of aggressive technogenic waters.